Network architecture with intrinsic security - Weiyu JIANG; Bingyang LIU; Chuang WANG (Dianxin kexue)
IP network brings big benefits for human’s life by connecting most devices all over the world,but its security and privacy issues make people frustrating when using end to end communication.Without intrinsic security design of the network,it is difficult for patch-like solutions to cure stubborn security issues (IP spoofing,privacy leakage,MITM attack,DDoS,etc.).On the basis of surveying different kinds of security threats and related security techniques,an overview of the security weakness analysis was given,and network architecture with intrinsic security (NAIS) was presented,including dynamic ID/IP with intrinsic security,security verification and audit protocols,and cross-domain cooperation defense mechanism,which could provide security and trustworthiness for end to end communication.